2023
DOI: 10.1007/s00737-023-01316-1
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use disorder as a risk factor for violent offending and reoffending in delinquent women with substance use disorders

Abstract: Female gender is generally less associated with aggressive behavior and violent offending than male gender. Therefore, most studies on violence and (re-)offending include only men. However, it is crucial to better understand pathways to female offending in order to enable efficient psychological interventions and risk assessment in women. Well-established risk factors for aggressive behavior include alcohol use disorder (AUD) and other substance use disorders (SUDs). We retrospectively analyzed the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…While studies identified alcohol as one of the main factors influencing reoffending and violent crimes overall in forensic psychiatric patient populations in both sexes/genders [29][30][31], we were able to extend these prognostic factors. Particularly, the present findings show that a violent index crime as well as physical aggression during the hospitalization period did indeed serve as negative predictors of violent reoffending in the addiction group.…”
Section: Discussionmentioning
confidence: 73%
“…While studies identified alcohol as one of the main factors influencing reoffending and violent crimes overall in forensic psychiatric patient populations in both sexes/genders [29][30][31], we were able to extend these prognostic factors. Particularly, the present findings show that a violent index crime as well as physical aggression during the hospitalization period did indeed serve as negative predictors of violent reoffending in the addiction group.…”
Section: Discussionmentioning
confidence: 73%
“…Among those who reported past-year AUD, pregnant and parenting women had a higher prevalence of treatment relative to the not pregnant, not parenting women (see Table 2). Treatment was modestly patterned by age, with the oldest group age (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) most likely to receive treatment (5.3%, 95%CI: 4.3-6.4), followed by the middle age group (ages 26-34 years; 4.9%, 95%CI: 3.8-6.1) and then the youngest (ages 18-25; 3.3.%, 95%CI: 2.6-4). Women with less than high school education and those in the lowest annual household income category had a higher treatment prevalence (8.0%, 95%CI: 5.8-10.2 and 7.1%, 95% CI: 5.4-8.8 respectively) relative to their counterparts with higher education or household incomes.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…History of arrests displayed the strongest association with both AUD and AUD treatment. The link between alcohol misuse and criminal behavior may be bidirectional, with AUD increasing the likelihood of engaging in criminal activities [37] and involvement with the criminal justice system increasing the risk of substance use disorders [38]. Women with a history of arrests may have encountered legal consequences related to their substance use, such as courtmandated treatment or probation requirements [39][40][41].…”
Section: Plos Onementioning
confidence: 99%
“…Another study examining gender differences in violent offending also revealed lower educational achievement, adverse childhood experiences, and mental health issues to be more prevalent in women ( 24 ). Further risk factors include self-harm ( 25 ), low self-esteem ( 8 ) and alcohol use disorder ( 26 ).…”
Section: Introductionmentioning
confidence: 99%